The Effectiveness of Using LibreOffice Impress on Improving Arts and Culture Learning Outcomes of Grade XI Students at SMAN 4 Sidrap - Cahya Dwi Anugrah; Madaling Madaling; Muhammad Takdir; Nurmayanti Nurmayanti (Universitas Muhammadiyah Enrekang, 2025)
This study employed a quantitative method with an experimental research design aimed at determining the effectiveness of using LibreOffice Impress media in improving the Arts and Culture learning outcomes of Grade XI students at SMAN 4 Sidrap. The population of this research consisted of all 75 students of Grade XI at SMAN 4 Sidrap, with a sample of 17 students. The data collection techniques used were documentation, tests, and questionnaires. After collecting the data, the researcher analyzed the results and found that all effectiveness indicators of a strategy had been met, showing that the use of LibreOffice Impress media had a positive effect on improving student learning outcomes in Arts and Culture subjects for Grade XI students at SMAN 4 Sidrap. The findings of the study revealed that the use of LibreOffice Impress was effective in improving students’ learning outcomes. This was proven through the results of the paired sample t-test between the pretest and posttest data, which indicated significant differences in students’ learning outcomes. The average posttest score (Mx = 90) was higher than the average pretest score (My = 45). Therefore, it can be concluded that the use of LibreOffice Impress is effective in improving the Arts and Culture learning outcomes of Grade XI students at SMAN 4 Sidrap